IS HOMEOSTASIS MODEL ASSESSMENT FOR INSULIN RESISTANCE >2.5 A DISTINGUISHED CRITERIA FOR METABOLIC DYSFUNCTION-ASSOCIATED FATTY LIVER DISEASE IDENTIFICATION? - BARRETO,Bárbara Ferreira de Mello (2022)
ABSTRACT Background Insulin resistance (IR), assessed by different criteria, is an important factor in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). More recently with the characterization of this metabolic dysfunction-associated fatty liver disease (MAFLD), one of the proposed criteria for this diagnosis has been the determination of the homeostasis model assessment-insulin resistance (HOMA-IR). Objective: The purpose of this study was to evaluate the relationship of HOMA-IR>2.5 with clinical, metabolic, biochemical and histological data obtained in non-diabetic patients diagnosed with NAFLD by liver biopsy. Methods: Cross-sectional, retrospective study was carried out with data from 174 adult individuals of both genders with non-diabetics NAFLD, without obvious signs of portal hypertension. The body mass index (BMI) was classified according to the World Health Organization (1998), and the metabolic syndrome by the criteria of NCEP-ATP-III. Biochemical tests were evaluated using an automated method and insulinemia through immunofluorometric assay. Histological findings were classified according to Kleiner et al. (2005). Results: The mean age of the studied population was 53.6±11.2 years, with 60.3% being female. The average BMI was 30.3 kg/m2 and 75.9% of the patients had increased waist circumference. Among evaluated metabolic parameters, there was a higher prevalence of metabolic syndrome (MS) in patients with HOMA-IR>2.5, with no statistical difference in relation to BMI between studied groups. Values of liver enzymes and serum ferritin were significantly higher in patients with this marker of IR, who had a higher prevalence of non-alcoholic steatohepatitis (NASH) and advanced liver fibrosis. In the multivariate analysis, the clinical diagnosis of MS, hyperferritinemia and the presence of NASH in the liver biopsy were the factors independently associated with the presence of altered HOMA-IR. Conclusion: HOMA-IR values >2.5 identify patients with NAFLD with distinct clinical and metabolic characteristics and with a greater potential for disease progression, which validates this parameter in the identification of patients with MAFLD.